Peninggalan Perang Dunia II di Teluk Youtefa Penyelamatan dan Pelestariannya - Marlin Tolla (BALAI ARKEOLOGI PAPUA, 2009)
A lot of world II remains was laid on Youtefa bay, a long time ago the the battle between Japan allied was happed here. Now this place is really anxious because the world war II remains are lost into the sea and some part of the battle ship are stole. This problem maybe solve with preservation and conservation because this place is potential to be a tourism place and can give a contribution for the public and real government.